2003
DOI: 10.1046/j.1540.8167.90308.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Unipolar Electrogram Morphology in a Computer Model of Atrial Fibrillation

Abstract: Analysis of the amplitude and symmetry of unipolar atrial electrograms can provide information about the electrophysiologic substrate maintaining AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 21 publications
7
101
0
Order By: Relevance
“…The LA and RA are connected through 3 interatrial connections: the Bachmann's bundle, fossa ovalis, and coronary sinus as observed with simultaneous biatrial noncontact mapping in humans. 13 By assigning different diffusion coefficients, as suggested previously, 8,12 we obtained heterogeneous conduction regions in the atria ( Figure IIB in the online-only Data Supplement). Specifically, the conduction velocities were 65 cm/s in the bulk tissue, 120 cm/s in the fast bundles, and 36 cm/s in the slow-conduction region.…”
Section: Atrial Anatomic Structuresupporting
confidence: 53%
See 4 more Smart Citations
“…The LA and RA are connected through 3 interatrial connections: the Bachmann's bundle, fossa ovalis, and coronary sinus as observed with simultaneous biatrial noncontact mapping in humans. 13 By assigning different diffusion coefficients, as suggested previously, 8,12 we obtained heterogeneous conduction regions in the atria ( Figure IIB in the online-only Data Supplement). Specifically, the conduction velocities were 65 cm/s in the bulk tissue, 120 cm/s in the fast bundles, and 36 cm/s in the slow-conduction region.…”
Section: Atrial Anatomic Structuresupporting
confidence: 53%
“…Both are within the range of atrial refractory periods in humans 7 and are comparable to previous modeling studies of atrial arrhythmias. 8 …”
Section: Methods the Single-cell Modelmentioning
confidence: 99%
See 3 more Smart Citations